Uremia modulates the phenotype of aortic smooth muscle cells. (February 2017) - Madsen, Marie; Aarup, Annemarie; Albinsson, Sebastian; Hartvigsen, Karsten; Sørensen, Charlotte M.; Turczynska, Karolina; Nielsen, Lars B.; Pedersen, Tanja Xenia
Abstract: Background and aims: Chronic kidney disease leads to uremia and markedly accelerates atherosclerosis. Phenotypic modulation of smooth muscle cells (SMCs) in the arterial media plays a key role in accelerating atherogenesis. The aim of this study was to investigate whether uremia per se modulates the phenotype of aortic SMCs in vivo . Methods: Moderate uremia was induced by 5/6 nephrectomy in apolipoprotein E knockout ( ApoE -/- ) and wildtype C57Bl/6 mice. Plasma analysis, gene expression, histology, and myography were used to determine uremia-mediated changes in the arterial wall. Results: Induction of moderate uremia in ApoE -/- mice increased atherosclerosis in the aortic arch en face 1.6 fold ( p  = 0.04) and induced systemic inflammation. Based on histological analyses of aortic root sections, uremia increased the medial area, while there was no difference in the content of elastic fibers or collagen in the aortic media. In the aortic arch, mRNA and miRNA expression patterns were consistent with a uremia-mediated phenotypic modulation of SMCs; e.g. downregulation of myocardin, α-smooth muscle actin, and transgelin; and upregulation of miR146a. Notably, these expression patterns were observed after acute (2 weeks) and chronic (19 and 30 weeks) uremia, both under normo- and hypercholesterolemic settings. Functionally, aortic constriction was decreased in uremic as compared to non-uremic aorta segments, as measured by myography. Conclusions: Uremia modulates the phenotype of aortic SMCs as determined by mRNA/miRNA expression, an increased medial area, and decreased aortic contractility. We propose that this phenotypic modulation of SMCs precedes the acceleration of atherosclerosis observed in uremic mice. Highlights: Accelerated atherosclerosis and increased systemic inflammation. Phenotypic modulation of smooth muscle cells in the aorta. Decreased aortic contractility.